N,N'-Bis(phenyl-carbamo-thio-yl)benzene-1,3-dicarboxamide - Zainab, Ngaini; Maya Asyikin, Mohd Ariff; Wan Sharifatun Handayani, binti Wan Zullkiplee; Hasnain, Hussain; Mohd Mustaqim, Rosli (International Union of Crystallography, 2013)
The asymmetric unit of the title compound, C22H18N4O2S2, contains two molecules. In one of them, the dihedral angles between the central benzene ring and the phenyl rings are 16.97 (8) and 20.97 (8), while the phenyl rings make a dihedral angle of 37.87 (8). In the other molecule, the corresponding values are 34.92 (7), 53.90 (7) and 60.68 (8), respectively. In each molecule, two intramolecular N—H O hydrogen bonds generate S(6) rings and a short C—H S contact also occurs. In the crystal, N—H S, N—H O, C— H O and C—H S interactions link the molecules into a three-dimensional network.